Pregnancy as a natural model of allograft tolerance. Interactions between adherent macrophages and trophoblast populations. - Lu, C; Redline, R; Shea, C; Dustin, L; McKay, D (1989)
From an immunologic viewpoint, the fetus with its paternal antigens may be considered a successful allograft in the maternal host. Understanding the basis of this host-allograft relationship remains a fundamental unsolved problem in transplantation immunobiology. We have previously demonstrated that local immunoregulation in the murine placenta prevented macrophage activities necessary for an effective response against the intracellular bacterium Listeria monocytogenes. Given the central role of macrophages both as antigen-presenting and cytolytic effector cells, such local immuno-regulation may ordinarily help prevent rejection of the fetoplacental unit with its paternal alloantigens by the maternal immune system. We therefore examined two types of interaction between macrophages and the placental cells that populate the maternal-fetal interface. (1) Upon activation to kill listeria efficiently, macrophages also acquire cytolytic capacities against some tumor and embryonic cells. We tested the hypothesis that macrophage activation in the placenta was inhibited to prevent macrophages from lysing fetal trophoblasts. We found, however, that trophoblasts isolated by dispase dispersion, differential isopyknic centrifugation, and adherence were not lysed by three different populations of cytolytic macrophages: (a) those activated in vivo during listeriosis, (b) peptone-elicited macrophages activated in vitro by recombinant interferon gamma and other lymphokines, and (c) the macrophage cell line RAW 264.7 activated in vitro. (2) Previous studies had demonstrated that cells from the placental region and their conditioned media inhibited a variety of lymphocyte functions. However, we found that these did not inhibit activation of adherent macrophages as assessed by induction of cell-surface Ia and acquisition of tumoricidal activity. In addition, under conditions where placental cells inhibited the proliferative response of a cloned CD4+ anti-Listeria T cell line to fixed, antigen-pulsed macrophages, the secretion of macrophage-activating lymphokines was not affected. These studies are important because they indicate that previously described suppressor systems in the murine placental region do not account for the profound local deficits in macrophage function seen during listeriosis.